The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1136/rmdopen-2017-000527
|View full text |Cite
|
Sign up to set email alerts
|

Synovial tissue macrophages: friend or foe?

Abstract: Healthy synovial tissue includes a lining layer of synovial fibroblasts and macrophages. The influx of leucocytes during active rheumatoid arthritis (RA) includes monocytes that differentiate locally into proinflammatory macrophages, and these produce pathogenic tumour necrosis factor. During sustained remission, the synovial tissue macrophage numbers recede to normal. The constitutive presence of tissue macrophages in the lining layer of the synovial membrane in healthy donors and in patients with RA during r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 93 publications
(140 reference statements)
1
92
0
2
Order By: Relevance
“…Moreover, defective regulatory T cells are associated with autoimmune disorders, such as RA [46]. Furthermore, macrophages play an active role in the pathogenesis of inflammatory arthritides because of the high expression of pro-inflammatory cytokines and matrix metalloproteinases, and they are APCs for T cells and B cells, representing a source of osteoclast precursors in an inflammatory context [47]. Lymphocytes infiltrate the synovium, where aggregates of T cells and B cells are found, and their absence is associated with remission [48,49].…”
Section: Oxidative Stress and Inflammation In Arthritismentioning
confidence: 99%
“…Moreover, defective regulatory T cells are associated with autoimmune disorders, such as RA [46]. Furthermore, macrophages play an active role in the pathogenesis of inflammatory arthritides because of the high expression of pro-inflammatory cytokines and matrix metalloproteinases, and they are APCs for T cells and B cells, representing a source of osteoclast precursors in an inflammatory context [47]. Lymphocytes infiltrate the synovium, where aggregates of T cells and B cells are found, and their absence is associated with remission [48,49].…”
Section: Oxidative Stress and Inflammation In Arthritismentioning
confidence: 99%
“…Activated macrophages promote a number of proinflammatory mechanisms in the RA synovium through abundant secretion of proinflammatory cytokines; in addition, macrophages induce nitric oxide synthase, present antigen to T and B cells and drive bone resorption [41]. RA synovial CD68 + macrophages correlate strongly with mitochondrial dysfunction and oxidative stress and are inversely related to in-vivo synovial pO2 levels [11,12,20].…”
Section: The Role Of Monocyte and Macrophage Metabolism In Ramentioning
confidence: 99%
“…M2-like macrophages can be induced ex vivo by incubation in the presence of M-CSF supplemented or not with IL-4-IL-13 or of macrophage medium containing human serum AB (SAB) and have diverse functions, ranging from parasite control to immune suppression, wound repair, tissue remodeling, and angiogenesis (11). Some studies have clearly demonstrated that infiltrating synovial macrophages display a proinflammatory profile (2,(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%